2004
DOI: 10.1080/j003v18n01_03
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Web-Based Supports for Occupational Therapy Students During Level II Fieldwork

Abstract: SUMMARY Occupational therapy students often experience high levels of anxiety about transitioning from the academic student role to the fieldwork student role. The separation from their classmates and the geographical relocation may isolate some students. Additionally, the quality and quantity of on-site supports available to individual students vary with each placement. A web-based resource was designed to assist occupational therapy students from the University of South Alabama with the transition from stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…As we come to understand more about the processes and elements of clinical reasoning, and as services users continue to take up opportunities to be included in the clinical reasoning process, the process of teaching clinical reasoning becomes more demanding (Higgs & Jones, 2008; Ryan & Higgs, 2008; Schell & Schell, 2008a). A number of authors have described the potential benefits of online interactions to support the development of a range of skills, including clinical reasoning (Creel, 2001; Hollis & Madill, 2006; Murphy, 2004; Thomas & Storr, 2005; Wooster, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As we come to understand more about the processes and elements of clinical reasoning, and as services users continue to take up opportunities to be included in the clinical reasoning process, the process of teaching clinical reasoning becomes more demanding (Higgs & Jones, 2008; Ryan & Higgs, 2008; Schell & Schell, 2008a). A number of authors have described the potential benefits of online interactions to support the development of a range of skills, including clinical reasoning (Creel, 2001; Hollis & Madill, 2006; Murphy, 2004; Thomas & Storr, 2005; Wooster, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A number of such programmes designed to support occupational therapy students undertaking fieldwork have been described in the literature. These programmes have used various interaction methods, including asynchronous discussions (Scanlan, McLoughlin & Hancock, 2006; Thomas & Storr, 2005; Trujillo & Painter, 2009), synchronous discussions (Creel, 2001) and email listservs (Wooster, 2004). Most investigators have reported that students found online interactions during fieldwork useful for maintaining contact with peers and university staff (Creel, 2001; Scanlan, McLoughlin & Hancock, 2006; Thomas & Storr, 2005; Trujillo & Painter, 2009; Wooster, 2004) and to discuss clinical and personal experiences (Creel, 2001; Trujillo & Painter, 2009; Wooster, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature revealed some support for the use of online instructional delivery to facilitate or enhance existing clinical reasoning among occupational therapy students during fulltime clinical rotations after the completion of their didactic course work (Creel, 2001;Murphy, 2004;Scanlan & Hancock, 2010, Thomas & Storr, 2005Trujillo & Painter, 2009;Wooster, 2004). The study conducted by Scanlan and Hancock (2010) explored online synchronous and asynchronous interaction of students completing clinical rotations, and reported that the participants demonstrated increased depth in clinical reasoning (procedural reasoning), understanding of the diagnostic presentation of clients (procedural or scientific reasoning), problem solving client cases, and implementation of occupational therapy interventions.…”
Section: Narrative Reasoningmentioning
confidence: 99%